THE INFLUENCE OF GLOBALIZATION ON ECONOMIC GROWTH - Riak , Dr. Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Globalization is a multidimensional phenomenon that not only touches political, economic, social and cultural spheres of any society but also reshapes the traditional way of studying the “social world and human nature (Crafts, 2014). Globalization is often associated with “intensification of the worldwide social relations”, global economic integration, de-territorialization and time-space compression (Bhandari, Amit and Heshmati, 2014).There is no universal acceptable definition of globalization as different scholars define it based on their understanding and at certain point in time which makes the meanings far from consistent. Ibrahim, (2015) define Globalization as the growing influence that exerted at the local, national, and regional levels by financial, economic, environmental, political, social, and cultural processes that are interconnected in scope.